HISTOLOGICAL CHANGES IN THE HEART AND THE PROXIMAL AORTA IN STREPTOZOTOCIN-INDUCED DIABETIC RATS FOLLOWING PIPER SARMENTSOUM ADMINISTRATION - Thent, Zar Chi; Lin, Teoh Seong; Das, Srijit; Zakaria, Zaiton (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Cardiovascular complications are one of the leading causes of deaths in diabetes mellitus. Piper sarmentosum (P.s) is known to possess antihyperglycaemic effects. The aim of the study was to observe the histological changes in the heart and the proximal aorta of streptozotocin-induced diabetic rats following P.s administration. Twenty-four male Sprague-Dawley rats (n=24) were equally randomized into four groups: control group supplemented with normal saline (C); control group supplemented with P.s (CTx) ; diabetic group supplemented with normal saline (D) and, diabetic group supplemented with P.s (DTx). Diabetes was induced by STZ (50mg/kg body weight) intramuscularly. P.s extract (0.125g/kg) was administered orally for 28 days, following four weeks of STZ induction. The cardiac and aortic tissues were collected and viewed under different staining: Haematoxylin and Eosin (H & E), Verhoeff-van gieson (VVG), Masson’s Trichome (MT) and Periodic Acid- Schiff (PAS) stains. There were abnormal cardiomyocytes nuclei, disarray of myofibres and increase in connective tissue deposits in cardiac tissues of the diabetic untreated group. The thickness of tunica media and ratio of tunica intima to media were found to be significantly increased in aorta of diabetic untreated group (P < 0.05) compared to the control group. There were degenerative changes of the proximal aortic tissues in diabetic untreated group. All the histological damages of cardiac and aortic tissues were found to be lesser in diabetic treated group. Supplementation with P.s extract prevented the oxidative damage arising from diabetes mellitus and its complications.